International labor migration and women's status of the left behind the case of Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
While the role of remittance sent by the migrant labors on economic development of the sending communities has received much attention, the non-economic consequences of international migration on the left behind family members have not adequately explored. By extracting data from a demographic surveillance system, this article examines the social impact of the international migration on women's status of the sending communities in rural Bangladesh. Findings reveal that the remittance sent by the migrant labors has not only raises the living condition of the left behind but also the diffusion of secular ideas along with remittance significantly modifies the traditional behavior of the sending communities. Women's role in managing the household affairs and control of the remittance sent to them substantially raise their social position within the family. The study concludes that the social and economic aspects of overseas migration raises the status of the left behind women by enhancing the individual position in their families and modifying the cultural values of the communities. Compared to earlier permanent moves, the contemporary international migration is primarily 'southnorth' temporary flow oflabors (United Nations, 1985) although the migrants include a wide spectrum of population including high skilled professionals to low paid laborers. South-north international migration not only produces large inflows of valuable remittance that stimulate economic growth but helps reducing unemployment and poverty at the sending communities (Russell, 1997). Policy-makers of the less developed countries are convinced that exporting labor to developed countries stimulates their economic growth (Russell, 1997; Simmons, 1984). While the role of remittance sent by the migrant labors on economic development of the sending communities has received much attention, the non-economic consequences of labor migration on the left behind family members have not adequately explored (Shah and Arnold, 1985).